PEMBERDAYAAN MASYARAKAT DENGAN PEMANFAATAN OLAHAN SUKUN UNTUK PENCEGAHAN ANEMIA PADA REMAJA DI BANTARAN SUNGAI MARTAPURA - Rifqoh Rifqoh; Jujuk Anton Cahyono; Yayuk Kustiningsih (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2026)
Anemia in adolescent girls is an important public health problem with both short- and long-term consequences. The main causes of anemia in this group are inadequate nutritional intake, particularly protein and iron, as well as blood loss during menstruation. This condition not only reduces concentration and productivity but also affects reproductive readiness. If not addressed early, adolescent girls with anemia are at risk of giving birth to infants with low birth weight, undernutrition, and even stunting. This community service program aimed to empower adolescent girls and village cadres through the utilization of local food made from breadfruit (Artocarpus altilis) as an effort to prevent anemia. The implementation methods included: (1) health education on anemia in adolescent girls and the importance of balanced nutrition; (2) training on breadfruit-based food processing, particularly the innovation of breadfruit risoles; (3) establishment of the community group “Pioneers of Anemia-Free Adolescent Girls” as agents of program sustainability; and (4) evaluation of participants’ knowledge using pre-test and post-test instruments.The results showed a 45% increase in participants’ knowledge after the training sessions, along with high enthusiasm during the breadfruit risoles preparation practice. The local food product received positive responses and was considered to have potential as a nutritious food alternative as well as a household business opportunity. The establishment of a community group was also a significant step in ensuring the sustainability of adolescent health education programs. In conclusion, this activity contributes to strengthening the preparedness of adolescent girls as future mothers, thereby supporting the birth of a stunting-free generation through nutrition interventions based on local food potential.